Study of Current - Voltage Characteristics of Normal and Abnormal Glow Discharge in Air at Low Pressures - Ahmed Y. Owaid (Tikrit Journal of Pure Science)
In the present study experimental measurements have been carried out to investigate the variation of air discharge voltage (V) and current (I) as a function of working pressure (p), in the ranges (300-500 V), (2-15 mA) and (0.09-0.13 Torr) respectively. Two thick, flat and circular electrodes of radius  (4 cm) of Aluminum with a Pyrex cylinder tube of length (10 cm) and radius  (3.5 cm) were used to generate the air glow discharge modes. The (V-p) characteristics have shown that an increasing in the discharge voltage of normal mode and reduction in that of abnormal mode with increasing the working pressure. It also displayed that the range of upper voltage from breakdown to abnormal glow has a minimum value (15.7 V) at  (0.117 Torr). In addition to that, it is found that  the (I-V) characteristics of air glow discharge modes  are consistent with those reported in the literature for other gases, as argon, hydrogen and oxygen. It is expected that these observations can help to reduce the voltage needed to get an intense abnormal glow discharge in the air, and to understand well the behavior of two modes of glow discharge, that is important in various applications.